Modal and Stability Finite-element Analysis of 160 km/h Track Car Body - 吴丹; 商跃进; 王红; 郭富强 (机车电传动)
Against the problem of high-speed rail car body steel structure dynamic characteristics declining, the model of the steel structure of car body for domestic 160 km/h track car was studied.Based on the theory of vehicle dynamics and finite element simulation techniques, the dynamic characteristics of car body were analyzed, improving means of car body dynamic performances were put forward. The results showed that the car body satisfied the technic specification. In order to make dynamical characteristic of ar body better, the dimension and structure of car body should be optimized yet.